2016
DOI: 10.14720/aas.2016.107.1.09
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exogenous polyamines on antioxidant defence and essential oil production in valerian (Valeriana officinalis L.) plants under drought stress

Abstract: The objective of this study was to determine the effects of foliar application of polyamines (PAs) on antioxidant defence and essential oil production of valerian (<em>Valeriana officinalis</em> L.) grown under different drought stress treatments (100, 70, 50 and 30% available water content). This study was carried out using pots in greenhouse condition. Drought–stressed valerian seedlings were sprayed with 1 mM concentration of each putrescine (Put), spermidine (Spd) and spermine (Spm). The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 34 publications
(32 reference statements)
3
4
0
Order By: Relevance
“…However, very severe drought stress conditions (30% available water content) led to reverse trends. Although the exogenous application of polyamines (growth regulators) was ineffective on EO accumulation, it alleviated reverse effects of stress on plants by increasing root growth and consequently improving EO yield [330]. These results are in line with another study, where reduction of valerian EO content induced by water stress was compensated by increasing root yield as a result of bio-fertilizer (rhizospheric bacteria and arbuscular mycorrhizal fungi) application [329].…”
Section: Valeriana Officinalissupporting
confidence: 82%
See 1 more Smart Citation
“…However, very severe drought stress conditions (30% available water content) led to reverse trends. Although the exogenous application of polyamines (growth regulators) was ineffective on EO accumulation, it alleviated reverse effects of stress on plants by increasing root growth and consequently improving EO yield [330]. These results are in line with another study, where reduction of valerian EO content induced by water stress was compensated by increasing root yield as a result of bio-fertilizer (rhizospheric bacteria and arbuscular mycorrhizal fungi) application [329].…”
Section: Valeriana Officinalissupporting
confidence: 82%
“…Results also indicated positive correlation between photosynthesis and EO content [ 328 ]. With regard to productivity optimisation in a scenario of drought and climate change, several publications evaluated the effect of drought stress on qualitative and quantitative traits of V. officinalis [ 329 , 330 ]. Root growth decreased with increasing water shortage, while the EO content was positively affected by moderate drought stress treatment (50% available water content).…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…Delayed leaf senescence was found to be associated with a higher Spm level, reduced reactive oxygen species (ROS) production (Sobieszczuk-Nowicka, 2017). Our results are in accordance with many studies (Amooaghaie and Moghym, 2011;Minocha et al, 2014;Mustafavi et al, 2016) where exogenous PAs alleviate growth inhibition possibly due to the protection of membranes and minimization of oxidative damage.…”
Section: Changes In Sugar Levelssupporting
confidence: 93%
“…Many changes during leaf senescence can be inhibited by the application of exogenous PAs (Cai, 2009). Accordingly, the maintenance of photosynthetic pigments in Spm-treated plants with enhanced growth and production is in accordance with Mustafavi et al, (2016). Chloroplasts are the first organ to undergo disorganization during leaf senescence, and chlorophyll catabolites are transported and accumulated in the vacuole (Ling and Jarvis, 2016).…”
Section: Changes In Photosynthetic Pigmentsmentioning
confidence: 87%
“…First, polyamines may play a critical role in drought stress signalling to confer adaptive responses (Pottosin and Shabala, 2014). Moreover, Mustafavi et al. (2016) reported that the polyamines control over the balance between ROS production and scavenging may “shape” H 2 O 2 signal.…”
Section: Discussionmentioning
confidence: 99%